Iridium-based hydride transfer catalysts: from hydrogen storage to fine chemicals. Issue 56 (11th June 2018) - Lu, Zhiyao; Cherepakhin, Valeriy; Demianets, Ivan; Lauridsen, Paul J.; Williams, Travis J.
Abstract : Selective hydrogen transfer remains a central research focus in catalysis: hydrogenation and dehydrogenation have central roles, both historical and contemporary, in all aspects of fuel, agricultural, pharmaceutical, and fine chemical synthesis. Abstract : Selective hydrogen transfer remains a central research focus in catalysis: hydrogenation and dehydrogenation have central roles, both historical and contemporary, in all aspects of fuel, agricultural, pharmaceutical, and fine chemical synthesis. Our lab has been involved in this area by designing homogeneous catalysts for dehydrogenation and hydrogen transfer that fill needs ranging from on-demand hydrogen storage to fine chemical synthesis. A keen eye toward mechanism has enabled us to develop systems with excellent selectivity and longevity and demonstrate these in a diversity of high-value applications. Here we describe recent work from our lab in these areas that are linked by a central mechanistic trichotomy of catalyst initiation pathways that lead highly analogous precursors to a diversity of useful applications.